Analisis Pengembangan Media Pembelajaran Berbasis Literasi Lingkungan untuk Peserta Didik Sekolah Dasar - utari akhir gusti; Rismawati Rismawati; Hufa Weno Artha; Noviandri Noviandri (Yayasan Indonesia Bermutu, 2022)
The COVID-19 pandemic has had a huge impact on various aspects of life. Environmental aspects are things that must be considered. This is in line with the demands of the 2013 Curriculum regarding environmental literacy in schools. The results of research conducted in several schools in the city of Padang revealed that there was still a lack of awareness of students in protecting the environment. This encourages teachers to develop learning media based on environmental literacy. This study aims to provide an overview of the importance of developing environmental literacy-based learning media in elementary schools. Data collection techniques with interviews and observation. This research is included in descriptive research with qualitative descriptive data analysis techniques. This research is important to do to increase awareness of students and the community in caring for and protecting the surrounding environment.